Capacity Building and Professionalism of PAUD Teachers in Banda District - Hermelina Abarua; Rosemaryn Tutupari; Prisca Diantra Sampe (CV. TOTUS TUUS, 2024)
Early Childhood Education Teachers are an important component in the world of education. A good teacher is a teacher who is able to be professional and apply concepts and plans appropriately in every learning process. By providing capacity building for PAUD teachers, it is hoped that participants will understand the basic concepts of PAUD and the importance of PAUD in education. PAUD TEACHER is able to understand the psychological condition and growth and development of children. PAUD TEACHER is able to do a good assessment of the needs of early childhood. In providing this activity using the training method where materials and activities are given in each session. The results obtained by the participants were able to understand the concept and be able to practice in each learning process. Thus the professionalism of PAUD teachers increases, meaning that the competence and quality of teachers also increases.